MULTILINGUALISM IN THE AGE OF GLOBALIZATION: CHALLENGES AND OPPORTUNITIES - Sugdiyona Tuychieva (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
Globalization has significantly influenced linguistic processes and communication worldwide. Multilingualism has become an important social and educational phenomenon in modern society. This article analyzes the challenges and opportunities of multilingualism in the era of globalization and highlights its role in education and intercultural communication.